2009
DOI: 10.3201/eid1503.080631
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin–producingEscherichia coliStrains Negative for Locus of Enterocyte Effacement

Abstract: Most Shiga toxin-producing Escherichia coli (STEC) infections that are associated with severe sequelae such as hemolytic uremic syndrome (HUS) are caused by attaching and effacing pathogens that carry the locus of enterocyte effacement (LEE). However, a proportion of STEC isolates that do not carry LEE have been associated with HUS. To clarify the emergence of LEE-negative STEC, we compared the genetic composition of the virulence plasmids pO113 and pO157 from LEE-negative and LEE-positive STEC, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 37 publications
5
42
0
Order By: Relevance
“…2). STEC plasmid-associated genes carried by p7v include enterohemolysin ehxCABD (2,(30)(31)(32), serine protease espP (2, 31), and catalase katP (4,(30)(31)(32). ETEC plasmidassociated genes carried by p7v include heat-stable enterotoxin sta and serine protease eatA (2,28,29).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). STEC plasmid-associated genes carried by p7v include enterohemolysin ehxCABD (2,(30)(31)(32), serine protease espP (2, 31), and catalase katP (4,(30)(31)(32). ETEC plasmidassociated genes carried by p7v include heat-stable enterotoxin sta and serine protease eatA (2,28,29).…”
Section: Resultsmentioning
confidence: 99%
“…While LEE-positive STEC plasmids are not as highly diverse as ETEC plasmids, LEE-negative STEC plasmids appear to exhibit great variation (4) but remain largely uncharacterized with the exception of pO113 (31). Additionally, the sequences of Escherichia sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The LEE island is not present in all STEC strains. Prior studies have found that EHEC is more commonly associated with severe clinical cases (6); however, LEEnegative STEC strains have been linked to severe clinical cases as well as to outbreaks (7). STEC is often acquired by consuming contaminated food or water (8), and cattle are viewed as the most important animal reservoirs (9).…”
mentioning
confidence: 99%
“…Well-known EHEC serotypes such as O157:H7, O26:H11, and O111:H8 all have eae and have caused severe disease. However, there are LEE-negative EHEC strains, such as O113:H21, that do not have eae but were first implicated in HUS in 1983 (4) and also caused a cluster of HUS cases in Australia in 1998 (5,6). Since O113:H21 strains are eae negative, they are postulated to have other binding factors and virulence genes (7).…”
mentioning
confidence: 99%